Acute Sympathetic Blockade Improves Insulin‐Mediated Microvascular Blood Flow in the Forearm of Adult Human Subjects With Obesity - Emily C. Smith; Jay N. Patel; Amr Wahba; Andrew Cluckey; Jorge Celedonio; JinWoo Park; LaToya Hannah; Suzanna Lonce; Cyndya A. Shibao; Sachin Y. Paranjape; Andre Diedrich; Owen McGuinness; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Obesity is associated with resistance to the metabolic (glucose uptake) and vascular (nitric‐oxide mediated dilation and microvascular recruitment) actions of insulin. These vascular effects contribute to insulin sensitivity by increasing tissue delivery of glucose. Studies by us and others suggest that sympathetic activation contributes to insulin resistance to glucose uptake. Here we tested the hypothesis that sympathetic activation contributes to impaired insulin‐mediated vasodilation in adult subjects with obesity. Methods and Results In a randomized crossover study, we used a euglycemic hyperinsulinemic clamp in 12 subjects with obesity to induce forearm arterial vasodilation (forearm blood flow) and microvascular recruitment (contrast‐enhanced ultrasonography) during an intrabrachial infusion of saline (control) or phentolamine (sympathetic blockade). Insulin increased forearm blood flow on both study days (from 2.21±1.22 to 4.89±4.21 mL/100 mL per min, P=0.003 and from 2.42±0.89 to 7.19±3.35 mL/100 mL per min, P=0.002 for the intact and blocked day, respectively). Sympathetic blockade with phentolamine resulted in a significantly greater increase in microvascular flow velocity (∆microvascular flow velocity: 0.23±0.65 versus 2.51±3.01 arbitrary intensity units (AIU/s) for saline and phentolamine respectively, P=0.005), microvascular blood volume (∆microvascular blood volume: 1.69±2.45 versus 3.76±2.93 AIU, respectively, P=0.05), and microvascular blood flow (∆microvascular blood flow: 0.28±0.653 versus 2.51±3.01 AIU2/s, respectively, P=0.0161). To evaluate if this effect was not due to nonspecific vasodilation, we replicated the study in 6 subjects with obesity comparing intrabrachial infusion of phentolamine to sodium nitroprusside. At doses that produced similar increases in forearm blood flow, insulin‐induced changes in microvascular flow velocity were greater during phentolamine than sodium nitroprusside (%microvascular flow velocity=58% versus 29%, respectively, P=0.031). Conclusions We conclude that sympathetic activation impairs insulin‐mediated microvascular recruitment in adult subjects with obesity.